Marsh Sedimentation Controls Delta Top Morphology, Slope, and Mass Balance - K. M. Sanks; S. M. Zapp; J. R. Silvestre; J. B. Shaw; R. Dutt; K. M. Straub (Geophysical Research Letters)
Abstract Rising sea levels, subsidence, and decreased fluvial sediment load threaten river deltas and their wetlands. However, the feedbacks between fluvial and non‐fluvial (marsh) deposition remain weakly constrained. We investigate how non‐riverine, elevation‐controlled deposition typified by marshes impacts sediment partitioning between a delta's topset, coastal zone, and foreset by comparing a delta experiment with proxy marsh accumulation to a control. Marsh accumulation alters fluvial sediment distribution by decreasing the slope in the marsh window by ∼50%, creating a 78% larger marsh zone. Fluvial incursions into the marsh window trap 1.3 times more clastic volume. The volume exported to deep water remains unchanged. Marsh deposition shifts elevation distributions toward sea level, which produces a hypsometry akin to field‐scale deltas. The elevation‐lowering effect of marshes on an equilibrium delta shown here constitutes an unexplored feedback and an important aspect of coastal sustainability.